Atomistic Study of the Bandgap Engineering of Two-Dimensional Silicon Carbide by Hydrogenation - Tran, Hanh Thi Thu; Nguyen, Phi Minh; Nguyen, Hoa Van; Chong, Tet Vui; Bubanja, Vladimir; Vo, Hoang Van (ACS Publications, 2023)
This work studied hydrogen adsorption by a two-dimensional silicon carbide using a combined molecular dynamics and density functional theory approach. The geometrical properties of partially and fully hydrogenated structures were investigated, considering the effect of zero-point energy. The preferred hydrogen atom location is on top of silicon atoms. The hydrogen interaction energies were obtained for the first time as the attractive force. For fully hydrogenated 2D SiC, the chair-like conformer is the most stable configuration, and the next is the boat-like conformer, while the table-like structure is not stable. The coverage and arrangement of the adsorbed hydrogen atoms significantly influence the values of the direct/indirect bandgaps of the considered systems, increasing the bandgap to 4.07, 3.64, and 4.41 eV for chair-like, table-like, and boat-like, respectively. Their dynamical stability was investigated by phonon dispersion calculations. The obtained results can serve as a guide for the application of hydrogenated two-dimensional silicon carbide in optoelectronic applications in manufacturing innovation.